Concurrent vs. immediate retrospective temporal sensory data collection: A case study on lemon-flavoured carbonated alcoholic drinks. (October 2022) - Visalli, Michel; Wakihira, Takahiro; Schlich, Pascal
Highlights: Descriptive temporal data were collected from consumers at home on smartphones. Retrospective and concurrent CATA descriptions over 3 periods were compared. The big picture was the same, but the retrospective panel was more discriminative. Retrospective measure should be considered in consumer studies. Abstract: Most temporal sensory methods measure product perception concurrently with tasting. However, retrospective measurement could have the advantage of being easier to implement with consumers. To date, no study has explicitly compared these two modes of temporal data acquisition. The objective of this study was to compare the temporal description obtained from consumers who had drank and evaluated a full can of four lemon-flavoured carbonated alcoholic drinks at home and on different days. The consumers were separated into two panels and asked to select from eight attributes on a check-all-that-apply list that were applicable during three periods of perception of a sip— "in mouth before swallowing", "immediately after swallowing" and "aftertaste"—for three sips of each can. The first panel (97 consumers) did the evaluation retrospectively immediately after the tasting (RET), while the second (96 consumers) did it concurrently with the tasting (SIM). Data were analysed using the multiple-response correspondence analysis (mrCA) framework applied at different levels: product, period and sip. The data from RET and SIM captured the differences between products and periods, with the differences between the products being larger than the differences between the periods. In both methods, no sip effect were observed. Perception of the products were identical in sips 1, 4 and 7. The consumers of RET and SIM agreed overall on the relative differences between products, although the level of discrimination was stronger for the consumers of RET. The consumers of RET and SIM only partially agreed on the between-period differences by product. The results suggest that the retrospective temporal evaluation could better discriminate the products and that the temporality patterns may be different between the two methods; therefore, there is a need for more research about the resolution of temporal data.